2024
DOI: 10.1027/1015-5759/a000753
|View full text |Cite
|
Sign up to set email alerts
|

Measurement Invariance of Children’s SEL Competencies

Abstract: Abstract. Although children use social and emotional learning skills (SEL) across the world, the expression of these skills may vary across cultures and developmental levels. Such variability complicates the process of assessing SEL competencies with consequences for understanding differences in SEL skills and developing interventions. To address these challenges, the current study examined the measurement invariance of translated versions of a brief, multi-informant (Teacher, Parent, Student) measure of SEL s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 43 publications
0
1
0
Order By: Relevance
“…Notably, the SSIS SELb was recently translated into Croatian as part of a large-scale six-country project called Promoting Mental Health at Schools (Anthony et al, 2023;Cavioni et al, 2023b;Cefai et al, 2022aCefai et al, , 2022b. The thorough translation process was followed up by initial validation evidence exploring measurement invariance (Anthony et al, 2023) and cross-country validity (Anthony et al, 2022b) evidence for scores from the Croatian version of the measure.…”
Section: The Ssis-sel Brief Scalesmentioning
confidence: 99%
See 2 more Smart Citations
“…Notably, the SSIS SELb was recently translated into Croatian as part of a large-scale six-country project called Promoting Mental Health at Schools (Anthony et al, 2023;Cavioni et al, 2023b;Cefai et al, 2022aCefai et al, , 2022b. The thorough translation process was followed up by initial validation evidence exploring measurement invariance (Anthony et al, 2023) and cross-country validity (Anthony et al, 2022b) evidence for scores from the Croatian version of the measure.…”
Section: The Ssis-sel Brief Scalesmentioning
confidence: 99%
“…Notably, the SSIS SELb was recently translated into Croatian as part of a large-scale six-country project called Promoting Mental Health at Schools (Anthony et al, 2023;Cavioni et al, 2023b;Cefai et al, 2022aCefai et al, , 2022b. The thorough translation process was followed up by initial validation evidence exploring measurement invariance (Anthony et al, 2023) and cross-country validity (Anthony et al, 2022b) evidence for scores from the Croatian version of the measure. Evidence was positive, providing a strong foundation for further validation and expansion in Croatia and other European countries, such as Romania, Italy, Portugal, Latvia and Greece (Colomeischi et al, 2022;Martinsone et al, 2022).…”
Section: The Ssis-sel Brief Scalesmentioning
confidence: 99%
See 1 more Smart Citation
“…The program has been designed both to enhance students' wellbeing and reduce their psychological difficulties, as well as to increase teachers' mental health by providing knowledge and practical tools on mental health promotion at school. Numerous studies have found that PROMEHS program increased students' mental health (Anthony et al, 2023;Anthony et al, 2022;Cefai et al, 2022b;Colomeischi et al, 2022;dos Santos et al, 2022); however, further research is required to evaluate its impact on teachers' mental health outcomes.…”
Section: Aims Of the Studymentioning
confidence: 99%
“…As mentioned earlier, the SSIS SELb were translated into six European languages for the PROMEHS program evaluation project. Measurement invariance and validity analyses were promising(Anthony et al, 2022b(Anthony et al, , 2023 in press) providing a solid basis for further extending the SSIS SELb to other countries, languages, and contexts. Two articles in this special issue specifically address this need for further evidence about the SSIS SELb.…”
mentioning
confidence: 99%